Modelling customers’ loyalty towards adopting Islamic mobile banking services - Mohd Thas Thaker, Mohamed Asmy; Amin, Md. Fouad Bin; Mohd Thas Thaker, Hassanudin; Allah Pitchay, Anwar; Khaliq, Ahmad (2019)
This study aims to find important factors of Malaysian Islamic banking customers’ loyalty or continuance intention to use Islamic mobile banking services. A total number of 250 customers of has participated in this research. Based on findings, continuance intention of using Islamic mobile banking services was found to be depended on usability of mobile banking services, customer service provided by Islamic banks towards mobile banking services, customer satisfaction on mobile banking services and trust of customers towards mobile banking services. In addition, mediating effect of Islamic mobile banking services continuance adoption significantly influenced by customer satisfaction and trust. By understanding these continuance intention factors among the customers, it would help the industry player particularly Islamic banking to plan and strategize appropriate policies, and support necessary programmes on diversifying and promoting financial transaction using mobile banking services among their existing and potential customers.